Analisis Karakteristik Lingkungan Pada Kejadian Leptospirosis di Kabupaten Demak Jawa Tengah Tahun 2009 - Ikawati, Bina; Nurjazuli, Nurjazuli (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2010)
Leptospirosis is a zoonosis disease caused by Leptospira bacteria and transmitted to human by contact withcontaminated animal urin or contaminated environment. Leptospirosis cases in Demak district increased for4 year later. Until April 15th 2008, there ware 62 leptospirosis cases with Case Fatality Rate =9,67%. The aimof this research was to determine environmental characteristic related to leptospirosis case in Demak district.It was an observational research using a case control design with 44 cases and 44 controls. Cases wereleptospirosis diagnosed by leptotek dri dot in Demak Health District Agency. Controls were neighbour ofleptospirosis cases who didnâ€™t have clinically symptom of leptospirosis, with age and sex at inclusion criteria.Laboratory diagnosis with leptotek dri dot had done for controls who agreed to sign inform consent. Datawere analyzed using chi square test at Î±=5%. Variable with p value<0,25 would be continued with multivariattest using Regressi Logistic - Backward Likehood Ratio method.The result of this research showed that there ware 10 controls with no clinical diagnosis but positive atleptotek dri dot diagnosis. At statistical analysis 10 cases and 10 controls dropped. Univariat analysis showedcontrols and cases have environmental risk factor and knowledge, attitude, practice about leptospirosissimilarly. Bivariat analysis showed there was no relationship between environmental characteristic andknowledge, attitude, practice with leptospirosis. Test of water sample had been done at 8 location. One ofthem of creek showed positif contain Leptospira sp. Rat trapped had been done at four location, showed trapsucces about 8,7%-29,8%. Eventhough environment factor and knowledge, attitude, practice showed therewere no relationship with leptospirosis statistically but water from creek that positif Leptospira sp, watersuffused and highly of trap succes at rat trapped were very conducive for leptospirosis transmission.Keywords : environment, leptospirosis, Demakpermalink: http://ejournal.undip.ac.id/index.php/mkmi/article/view/2912Â